Cyber notary in Islamic Economic Law in Indonesia - Ulfia Nur Faiqoh; Nynda Fatmawati Octarina (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This study discusses the application of cyber notary in sharia economic transactions in Indonesia, focusing on the challenges and potentials related to legal certainty. The main problems faced are how to maintain the validity of electronic contracts in accordance with the principles of sharia law, as well as challenges such as data protection, privacy, and digital infrastructure gaps. This research uses normative legal methods with legislative and conceptual approaches, as well as utilizing primary data sources from related regulations and secondary legal materials from academic literature. The results of the study show that cyber notary has great potential to increase efficiency and reduce costs in Islamic economic transactions. However, significant challenges related to electronic document verification and data security remain major obstacles. This research recommends the need for clearer harmonization of laws and regulations, improvement of digital infrastructure, and strengthening of the data security system. With these steps, cyber notary can be an effective instrument in supporting the development of sharia economic transactions, while still ensuring compliance with sharia principles such as honesty, fairness, and clarity. Thus, the implementation of cyber notary has the potential to bring positive changes in the Islamic economic legal system in Indonesia, provided that these challenges can be overcome effectively.